Analisis Politik Ruang Terbuka Hijau Studi Kasus pada Kecamatan Lamongan, Kabupaten Lamongan - M. Zimamul Khaq; Abdillah Qomaru Zaman (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This study seeks to explain: (1) How is environmental politics in the form of green open space development in Lamongan distict, Lamongan Regency (2) How is the dynamics of interests between actors in the practice of green open space development. The results that can be conveyed are (1) Development of green open space in Lamongan district until now is still not optimal; the ability of the community to actively participate in environmental management programs is very small. This condition has an impact on the function of green open space that has not been felt by the community and has an impact on aspects of maintenance that are not given attention. From the research results, the development of Green open space in Lamongan district is still dominated by private green open space which is more than 90%. Meanwhile, the allocation for green belt land use, parks and recreation areas is still not maximal. If we connect with the Minister of Public Works Regulation No. 5 of 2008, this is very far from expected because the ratio of green open space is 30 percent of the total area of ??Lamongan which reaches 1,782 km2 (2) District Government. Lamongan is currently still focusing on economic issues and putting aside environmental issues, especially green open space, therefore sustainable development is very difficult to carry out optimally in Lamongan district. The government in making spatial planning only prioritizes capitalist interests, and or more provides space andonly for investors.